Calculating set-volume for the limb muscles with the performance of multi-joint exercises: Implications for resistance training prescription - Schoenfeld, B. J.; Grgic, J.; Haun, C.; Itagaki, T.; Helms, E. R. (Sports, 2019)
Resistance training volume, determined by the number of sets performed (set-volume) is considered one of the key variables in promoting muscle hypertrophy. To better guide resistance exercise prescription for weekly per-muscle training volume, the purpose of this paper is to provide evidence-based considerations for set-volume ratios between multi-joint (MJ) and single-joint (SJ) exercises so that practitioners can better manage prescription of training volume in program design. We analyzed this topic from three primary areas of focus: (1) biomechanical and physiological factors; (2) acute research; and (3) longitudinal research. From a biomechanical and physiological standpoint, when considering force production of different muscle groups, the moment arm of a given muscle, "motor abundance", the link between biomechanics and exercise-induced fatigue, as well as the amount of time in voluntary muscle activation, a logical rationale can be made for SJ exercises producing greater hypertrophy of the limb muscles than MJ exercises (at least from specific exercises and under certain conditions). This would mean that sets for a MJ exercise should be counted fractionally for select muscles compared to an SJ exercise (i.e., less than a 1:1 ratio) when prescribing set-volumes for given muscles. When considering results from acute studies that measured muscle activation during the performance of SJ and MJ exercises, it seems that MJ exercises are not sufficient to maximize muscle activation of specific muscles. For example, during performance of the leg press and squat, muscle activation of the hamstrings is markedly lower than that of the quadriceps. These results suggest that a 1:1 ratio cannot be assumed. Current longitudinal research comparing the effects of training with MJ vs. SJ or MJ + SJ exercises is limited to the elbow flexors and the evidence is somewhat conflicting. Until more research is conducted to derive stronger conclusions on the topic, we propose the best advice would be to view set-volume prescription on a 1:1 basis, and then use logical rationale and personal expertise to make determinations on program design. Future research should focus on investigating longitudinal hypertrophic changes between MJ and SJ in a variety of populations, particularly resistance-trained individuals, while using site-specific measures of muscle growth to more systematically and precisely compute effective individualized set-volumes